Numerical modeling of liquid waste infiltration from storage facilities into surrounding groundwater and surface water bodies - Lyubimova, Tatiana Petrovna; Lepikhin, Anatoliy Pavlovich; Parshakova, Yanina Nikolaevna; Tsiberkin, Kirill Borisovich (Computational Continuum Mechanics, 2015)
The study focuses on infiltration of saturated brine from liquid waste storage facilities into the surrounding groundwater and surface water bodies. Storage facilities are located at the Verkhnekamsk Potassium and Magnesium Salt Deposit (Perm Region, Russian Federation) and contain highly mineralized brines of potassium, sodium and magnesium chlorides. Using the analytical solution of one-dimensional equation of contaminant transport by homogeneous stationary filtration flow, we have made estimates of the time it takes the contaminant to move from the storage facilities to the nearest surface water body and a settling time for the stationary concentration profile, neglecting and accounting for contaminant adsorption in the porous matrix. The contaminant concentration at the point of brine ingress into the surface reservoir is calculated. The direct 3D numerical modeling of brine infiltration into the surrounding medium is performed using ANSYS Fluent software package. The modeling results indicate different stages of contaminant propagation in the porous medium. It has been found that the contaminant spreads over a wide area with almost uniform concentration close to the saturation value. The contaminant reaches the nearest riverbed 20 days after the start of infiltration. The numerical results agree well with the analytical results obtained in the framework of the one-dimensional mode. The proposed physical models adequately describe hydrodynamic processes associated with the operation of large storage facilities and can be used to predict contamination propagation in groundwater around the storage facilities.